Antidiabetic activity of matoa leaves (Pometia pinnata J.R.Forst & G. Forst) extract on hyperglycaemic alloxan-induced rats - Wahyuni, Arifah Sri; Muflihah, Cita Hanif; Fadhilah, Arini; Oksaputra, Amar Khoiri; Ningrum, Nur Faizah Setya; Bakhtiar, Muhammad (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Matoa (Pometia pinnata J.R.Forst & G. Forst) leaves contain polyphenols and flavonoids which areprospective for the development of the new antidiabetic agent. This research aimed to explore thepotency of matoa leaves in reducing blood glucose level and increasing plasma insulin concentrationin alloxan-induced rats. The experimental study was done in 6 treatment groups: the aquadest (normal),alloxan (Alx) 150 mg/kgBW (negative control), glibenclamide (Gli) 5 mg/kgBW (positive control),and matoa leaves extract (MLE) at the doses of 50, 100, and 200 mg/kgBW. The treatment wasadministered for 14 days orally post-induction of alloxan and fasting blood glucose (FBG) reached>200 mg/dL. Blood glucose levels were established by the GOD-PAP (Diasys) method while plasmainsulin was measured using Rat insulin ELISA kit. Hematoxyline-eosin (HE) staining on tissues wasperformed to observe the population of pancreatic beta cells. The results showed that the MLE extractat a dose of 200 mg/kgBW could decrease the FBG level to 135.25±21.14 mg/dL and increase theplasma insulin level up to 0.14%. Pancreas histopathology indicated that the number of damaged cellswere lower than negative control. In conclusion, our results affirm the promising potential of MLE asa candidate of the novel antidiabetic agent.